Perencanaan Kerja Dan Kompetensi : Sebuah Studi Tentang Kinerja Pegawai - Masyita, Sitti; Gani, Mustafa; Djaharuddin, Dharmawaty; Rijal, Syamsul (P3M STIEM, 2022)
Thisistudyiaimsitoidetermineiwhetheritheiinfluence of work planning and competence affects the performance of the employees of the Department of Culture and Tourism of South Sulawesi Province. Data collection uses primary data obtained from distributing questionnaires using the Slovin formula which totals 58 respondents (customers). The results ofotheoquestionnaireihaveibeenitestediforivalidityiandireliabilityi, as well as tested classical assumptionsiin the form of normalityoassumptions, multicollinearity assumptions, heteroscedasticity, and autocorrelation. Methods of data analysis using multiple regression techniques.Based on the results of the analysis, it turns out that the research results show that the first hypothesis is accepted because it shows the results of the hypothesis testing have a significant positive effect. Means that the work planning makes a real contribution to the performance of the employees of the Culture and Tourism Office of South Sulawesi Province. The second hypothesis is accepted because it shows a significant positive hypothesis test results. It means that competence makes a real contribution to the performance of the employees of the Culture and Tourism Office of South Sulawesi Province. The third hypothesis is accepted because Work Planning and Competence have a simultaneous (together) effect on the Culture and Tourism Office of South Sulawesi Province.